2022
DOI: 10.1108/xjm-05-2022-0113
|View full text |Cite
|
Sign up to set email alerts
|

Why did I join networks? The moderating effect of risk-taking propensity on network linkage and the performance of women-owned businesses

Abstract: Purpose This study aims to contribute to the body of knowledge through focusing on the moderating effect of risk-taking propensity in the relationship between network linkage and business performance. Design/methodology/approach Exploratory factor analysis was conducted so as to verify the items. Furthermore, the direct and moderation tests were conducted through the PROCESS macro. Findings The findings revealed the propensity for risk-taking is a significant moderator of the relationship between network l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
2
6
0
1
Order By: Relevance
“…In a study by Westhead et al (2011), the results are also in line with the present study’s findings, as it states that entrepreneurs take calculated risks and are moderate risk-takers. This finding is also in alignment with the previous research studies conducted among micro-level women entrepreneurs conducted in Tanzania (Ismail, 2022) and in Pakistan (Zeb and Ihsan, 2020). It is also related to the entrepreneur’s motivation, age, education and business experience.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a study by Westhead et al (2011), the results are also in line with the present study’s findings, as it states that entrepreneurs take calculated risks and are moderate risk-takers. This finding is also in alignment with the previous research studies conducted among micro-level women entrepreneurs conducted in Tanzania (Ismail, 2022) and in Pakistan (Zeb and Ihsan, 2020). It is also related to the entrepreneur’s motivation, age, education and business experience.…”
Section: Discussionsupporting
confidence: 92%
“…The ability to grasp and identify suitable business opportunities and the desire to take calculated risks are good characteristics of successful entrepreneurs. Previous research demonstrates that women are less inclined than men to take risks, even when they have a same amount of competence and experience (Harris et al, 2006;Ismail, 2022). A study conducted among women entrepreneurs found that risktaking tendency found to improve business performance (Zeb and Ihsan, 2020).…”
Section: Incubationmentioning
confidence: 99%
“…Business networks are extensively viewed as an important ingredient to firms’ innovative capabilities, international enlargement, resources, learning, and recognition of emerging export opportunities (Lorenz et al, 2018; Pedersen et al, 2019). These networks occur based on ties like personal (like kinship and friendship), professional, religious, and business relationships (Ismail, 2022; Kazungu, 2020a; Olomi, 2009) and are also well-known for their role in integrating small firms’ supply chains in export markets and thus making them more effective and efficient in attracting more customers in foreign markets (Katsikeas et al, 2020). Likely, Business networks facilitate access to export information which contributes to strengthened business relationships and export market growth (Bianchi & Mathews, 2016).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Small enterprises are strongly regarded to be the major source of employment and industrialization. In developing countries like Tanzania, small enterprises are seen as the means of reducing the gap between the rich and the poor (Ismail, 2022a). However, research shows that there are some unfavorable conditions such as lack of resources, and poor technological bases which prevent small enterprises from realizing their full potential; thus resulting in failure to compete with large enterprise as well as imported goods (Ismail, 2022b).…”
Section: Introductionmentioning
confidence: 99%